Exciton quantum beats in GaAs/AlAs disk-shaped quantum dots - Le, Thi Dieu Hien; Le, Thi Ngoc Bao; Dinh, Nhu Thao (Hue University Journal of Science: Natural Science, 2023)
Using the renormalized wavefunction approach, we examined the excitonic quantum beat in a three-level system in disk-shaped quantum dots. The non-stationary electron wave function and the time-dependent exciton absorption intensity under the effect of an intensity pump laser that resonates with two excited electron states were also provided. Our numerical findings demonstrate that the time-dependent exciton absorption intensity takes the shape of a periodic oscillation when the quantum dot is subjected to a powerful resonant pump laser. This is clear evidence that quantum beats appears in the quantum disk. Additionally, the dot radius and the pump field detuning significantly affect the beat characteristics, such as frequency and amplitude.